Sedimentation Of Individual Molecules Of Heavy Elements In Initial Protoplanets (Journal of Bangladesh Academy of Sciences, 2012)
Segregation problem of individual molecules of heavy elements, has been reinvestigated determining the polytropic structure of a protoplanet. In this study the sedimentation time of different silicate grains having radii lying between 5 X 10-3cm and 1 cm was calculated. Settling times of the grains that came out through calculation could be found to be shorter than that of the time obtained by other authors. Key words: Segregation; Grain; Gravitational field; Protoplanet; Polytrope DOI: http://dx.doi.org/10.3329/jbas.v35i2.9422 JBAS 2011; 35(2): 179-186